Endothelial Progenitor and Mesenchymal Stromal Cells in Newborns With Congenital Diaphragmatic Hernia Undergoing Extracorporeal Membrane Oxygenation - Neysan Rafat; Neysan Rafat; Neysan Rafat; Christian Patry; Ursula Sabet; Tim Viergutz; Christel Weiss; Burkhard Tönshoff; Grietje Beck; Thomas Schaible (Frontiers Media S.A., 2019)
Background: Endothelial progenitor (EPC) and mesenchymal stromal cells (MSC) can regenerate damaged endothelium and thereby improve pulmonary endothelial dysfunction. We do not know, how extracorporeal membrane oxygenation (ECMO) might affect EPC- and MSC-mediated regenerative pathways in patients with congenital diaphragmatic hernia (CDH). Therefore, we investigated, if ECMO support impacts EPC and MSC numbers in CDH patients.Methods: Peripheral blood mononuclear cells from newborns with ECMO-dependent (n = 18) and ECMO-independent CDH (n = 12) and from healthy controls (n = 12) were isolated. The numbers of EPC and MSC were identified by flowcytometry. Serum levels of vascular endothelial growth factor (VEGF) and angiopoietin (Ang)-2 were determined.Results: EPC and MSC were elevated in newborns with CDH. ECMO-dependent infants had higher EPC subpopulation counts (2,1-7,6-fold) before treatment compared to ECMO-independent infants. In the disease course, EPC and MSC subpopulation counts in ECMO-dependent infants were lower than before ECMO initiation. During ECMO, VEGF serum levels were significantly reduced (by 90.5%) and Ang2 levels significantly increased (by 74.8%).Conclusions: Our data suggest that ECMO might be associated with a rather impaired mobilization of EPC and MSC and with a depression of VEGF serum levels in newborns with CDH.